Смертник: роман / Кирил Казанцев - Казанцев Кирилл (Оборотни в законе, 2010)
Экземпляры: ф.18 (2010) / Инвентарный номер: 46857 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 14 / ГРНТИ: 17.82.31 / ББК: 84(2Рус)6-44